The Satisfaction Of Jkn Participants Using The Indicator Of Hospital Consumer Assesment Of Healthcare Providers And System (HCAHPS) At Undata General Hospital - Pare Layuk, Debertus Barrang (Tadulako University, 2019)
Based on the Regulation of the Minister of Health of the Republic of Indonesia number: 129 / Menkes / Sk / II / 2008 concerning hospital minimum service standards (SPM) regarding inpatient satisfaction has a standard of> 90%. While for the BPJS patient satisfaction standard based on the JKN road map BPJS patient satisfaction> 75. The purpose of this study was to determine the Satisfaction of JKN Participants About the Quality of Health Services Using HCAHPS Indicators in the Inpatient Installation of Central Sulawesi Province Hospital. This type of quantitative research with a descriptive approach. The population in the study amounted to 7,083 respondents and the sampling used probability sampling with a total sample of 95 respondents. The results showed JKN participants' satisfaction with the HCAHPS method as follows: doctor's communication dimensions, satisfied (85.5%) and dissatisfied (10.5%). Dimensions of communication of nurses, satisfied (88.4%) and not satisfied (11.6%). Dimensions of the hospital environment, satisfied (84.2%) and dissatisfied (15.8%). Dimensions of pain management, satisfied (83.2%) and dissatisfied (16.8%). Dimensions of treatment communication, satisfied (83.2%) and dissatisfied (16.8%). Dimensions of recommendations to friends and family recommend (91.6%) and not recommend (8.4%). In conclusion, JKN participants were satisfied with all HCAHPS components studied.Â